Pheochromocytoma and stress cardiomyopathy: Insight into pathogenesis - Agrawal, Sahil (World J Cardiol, 2017)
AIM: To investigate the occurrence of cardiomyopathy (CMP) in a cohort of patients with histologically proven pheochromocytoma (pheo), and to determine if catecholamine excess was causative of the left ventricular (LV) dysfunction. METHODS: A retrospective chart review spanning years 1998 through 2014 was undertaken and patients with a diagnosis of pheo confirmed with histopathologic examination were included. Presenting electrocardiograms and cardiac imaging studies were reviewed. Transthoracic echocardiography (TTE), ventriculography or single positron emission computed tomography imaging was evaluated and if significant abnormalities [left ventricular hypertrophy (LVH) or LV dysfunction] were noted in the pre operative period a follow up post-operative study was also analyzed. Multivariate analysis using logistic regression was used to investigate independent predictors for outcomes of interest, LV dysfunction and LVH. RESULTS: We identified 18 patients with diagnosis of pheo confirmed on pathology. Mean age was 54.3 ± 19.3 years and 11 (61.1%) patients were females. 50% of such patients had either resistant hypertension or labile blood pressures during hospitalization, which had raised suspicion for a pheo. Cardiac imaging studies were available for 12 (66.7%) patients at the time of inclusion into study and preceding the adrenalectomy. 7 (58.3%) patients with a TTE available for review had mild or more severe LVH while 3 (25%) patients had LV dysfunction of presumably acute onset. In a multivariate analysis, elevated catecholamine levels as assessed by urinary excretion of metabolites was not an independent predictor of development of LV systolic dysfunction or of presence of LVH on TTE. Two female patients with a preceding history of hypertension had marked LV hypertrophy and systolic anterior motion of the mitral valve. Prolongation of the QTc interval was noted in 5 (27.8%) patients but no acute arrhythmias were observed in any patient. CONCLUSION: This study adds to the growing body of literature on the predilection of patients with pheochromocytomas to develop non-ischemic CMP. Degree of catecholamine excess as measured by urinary secretion of metabolites did not predict the development of CMP but 2 of 3 patients developed CMP in the setting of significant acute physiologic stress. Our findings provide support to the proposed etiologic role of elevated catecholamines in TC and other stress induced forms of CMP, however, activation of a brain-neural-cardiac axis from acute stress and local release of catecholamines but not chronic catecholamine elevations are likely to be responsible in pheo related CMP.